ANALISIS PROSEDUR PENGEMBALIAN BERKAS REKAM MEDIS RAWAT INAP GUNA MENUNJANG EFEKTIVITAS PELAYANAN - Hana Dhini Julia Pohan; Sri Agustina Meliala; Aida Sulisna (INFOKES (Informasi Kesehatan), 2022)
During a pandemic, BPJS Health increased digital-based innovation to make it easier to provide services to participants. One of them is an online queue system that is integrated into the Mobile-JKN application, making it easy for participants to access services at health facilities. This research was conducted with the aim of knowing the relationship between patient satisfaction with BPJS Kesehatan participants and online registration for the use of the Mobile-JKN application at Pratama Salma in November–December 2022. This research is analytic in nature, using primary and secondary data with a total sample of 30 BPJS participant patients' health at Pratama Salma Clinic in March–October 2022. From the results of the study it can be seen that 12 respondents 40.0% percent of BPJS Health Participating Patients are dissatisfied, most of the use of the Mobile application registration - Easy JKN is 12 respondents 40.0 percent while BPJS Health Participant Patients satisfied as many as 18 respondents 60.0 percent the majority use the Mobile application registration - JKN is easy as many as 10 respondents 33.3 percent, and the minority uses the Mobile application registration - JKN is not easy as many as 8 respondents 26.7 percent. The conclusion is expected: health workers will further improve communication and outreach in providing information, especially the advantages and disadvantages of using the mobile application for online registration (JKN). Keywords: BPJS Health Participant Satisfaction, Online Registration, JKN Mobile Application.